Identifikasi Serangan DDOS Pada Jaringan Komputer Menggunakan Algoritma Artificial Neural Network - Kelik Sussolaikah; Pitrasacha Adytia; Wahyuni Wahyuni; Lisda Aulia Rahmi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
DDOS (Distribute Denial of Service) is a type of structured attack. This attack has been around since 1990. DDoS attacks are capable of paralyzing servers by flooding network traffic and causing it to go down. To overcome this problem, the way to detect DDoS attacks has several methods and algorithms, one of which is the Artificial Neural Network algorithm and uses the Machine learning method due to the fast computing process, high accuracy, and this research uses the SKKNI research method Number 299 of 2020. The analysis was carried out uses training data from the latest dataset, namely CICIDS2017, which is a development of a previously existing dataset. DDoS attack detection testing using the confusion matrix method obtained bot precision of 0.99, recall of 0.99, and f1score of 0.99, 3